Pengaruh Komunikasi Internal dalam Membangun Budaya Organisasi - Nur Annisa Agustini; Ninuk Purnaningsih (Jurnal Komunikasi Pembangunan, 2018)
Internal communication can be understood as the foundation and building of an organizational culture. The existence of an organizational culture that has been firmly held by its employees will greatly support the process of the main purpose of the company. This research aims to analyze internal communication in building organization oriented on the results and time, using a sample of 30 respondents. This research is conducted by using quantitative approach supported by qualitative data. The results of this study indicate a change given by internal communication in building an organizational culture, which is one aspect is the leadership power that becomes a good example for the employees. A strong leadership role to provide direction and start with a good communication process, will get a positive response from its employees in work and improve the maximum work.